Personal finance management system - Cheok, Shen Yao (2024)
The "Personal Finance Management System" is a mobile application designed to help users manage their finances, make informed spending decisions, and plan for a secure financial future. This project addresses the need for better financial literacy by providing tools for budgeting, tracking expenses, saving, and planning for retirement. The main goal is to create a user-friendly mobile app that not only records and categorizes expenses, but also helps users in creating personalized budgets and offering spending recommendations. The system includes main features such as expense recording, spending guides, retirement planning, and expense analysis. The project integrates different aspects of personal finance management and follows proven budgeting and financial planning principles to provide users with accurate recommendations. This project aims to make a significant contribution to financial management by promoting informed spending, budgeting, and retirement planning. Thus, improving financial well-being and contribute to a more financially literate society.